A phase II trial of selumetinib in children with recurrent optic pathway and hypothalamic low-grade glioma without NF1: a Pediatric Brain Tumor Consortium study. Issue 10 (25th February 2021) - Fangusaro, Jason; Onar-Thomas, Arzu; Poussaint, Tina Young; Wu, Shengjie; Ligon, Azra H; Lindeman, Neal; Campagne, Olivia; Banerjee, Anu; Gururangan, Sridharan; Kilburn, Lindsay B; Goldman, Stewart; Qaddoumi, Ibrahim; et al.
Abstract: Background: Pediatric low-grade gliomas (pLGGs) are the most common childhood brain tumor. Progression-free survival (PFS) is much lower than overall survival, emphasizing the need for alternative treatments. Sporadic (without neurofibromatosis type 1) optic pathway and hypothalamic gliomas (OPHGs) are often multiply recurrent and cause significant visual deficits. Recently, there has been a prioritization of functional outcomes. Methods: We present results from children with recurrent/progressive OPHGs treated on a PBTC (Pediatric Brain Tumor Consortium) phase II trial evaluating efficacy of selumetinib (AZD6244, ARRY-142886) a MEK-1/2 inhibitor. Stratum 4 of PBTC-029 included patients with sporadic recurrent/progressive OPHGs treated with selumetinib at the recommended phase II dose (25mg/m 2 /dose BID) for a maximum of 26 courses. Results: Twenty-five eligible and evaluable patients were enrolled with a median of 4 (1-11) previous therapies. Six of 25 (24%) had partial response, 14/25 (56%) had stable disease, and 5 (20%) had progressive disease while on treatment. The median treatment courses were 26 (2-26); 14/25 patients completed all 26 courses. Two-year PFS was 78 ± 8.5%. Nineteen of 25 patients were evaluable for visual acuity which improved in 4/19 patients (21%), was stable in 13/19 (68%), and worsened in 2/19 (11%). Five of 19 patients (26%) had improved visual fields and 14/19 (74%) were stable. The most common toxicities were grade 1/2 CPK elevation, anemia, diarrhea, headache, nausea/emesis, fatigue, AST and ALT increase, hypoalbuminemia, and rash. Conclusions: Selumetinib was tolerable and led to responses and prolonged disease stability in children with recurrent/progressive OPHGs based upon radiographic response, PFS, and visual outcomes.